Appendix stump closure with titanium clips in laparoscopic appendectomy - Rickert, Alexander Lothar; Bönninghoff, Roderich; Post, Stefan; Kienle, Peter (Langenbeck's archives of surgery, 2012)
PurposeDifferent techniques, including clips, have been used to close the stump in laparoscopic appendectomy. The aim was to investigate the results after application of a newly developed titanium clip for this operation.MethodsFrom June 2008 to February 2010, 104 patients from two different hospitals undergoing laparoscopic appendectomy were included in this prospective study. Closure of the appendix base was generally intended with a titanium double-shanked clip (DS-Clip). The variables of interest were intra-and postoperative complications, operation time and hospital stay. Furthermore, an evaluation of the clip's practicability by the surgeon was performed using a standardised questionnaire.ResultsIn 104 patients screened intraoperatively, four patients had to be excluded as the operating surgeon felt that the clip was not adequate for closing the stump, generally because of severe inflammation of the base of the appendix with involvement of the caecum. One patient developed an intra-abdominal abscess which had to be drained interventionally; no reoperations were necessary. The overall complication rate, the operation time and the hospital stay were well comparable with other devices for appendix stump closure such as staplers, loops or polymeric clips. The practicability of the clip was mainly rated as excellent or good by the operating surgeons.ConclusionThis study suggests that the presented titanium DS-Clip is a safe and cost-effective technique for securing the appendix base in laparoscopic appendectomy. The application is easy and can be learned quickly, making it a good option also for teaching hospitals.